Body Composition and Physical Fitness in Madeira Youth - Diogo V. Martinho; Élvio Rúbio Gouveia; Cíntia França; Helder Lopes; Andreas Ihle; Adilson Marques; Ana Rodrigues; Ricardo Alves; Hugo Sarmento (Children, 2022)
Background: Research on composition and physical fitness is lacking in school-aged children from Madeira. This study aimed to examine the frequencies of overweight and obese participants and, in addition, to compare the fitness levels of Madeira youth with reference data. Methods: The sample comprised 521 participants (n = 258 boys; n = 263 girls) aged 10.0–18.9 years old. Methods: Height and weight were measured. Body mass index (BMI) was calculated, and percent fat was derived from skinfolds. Tests detailed on FITESCOLA battery were performed. BMI was plotted against U.S. reference data and physical assessment contrasted with the cut-off points of FITESCOLA protocol and corresponding data developed in Portuguese youth. Results: The percentages of overweight and obesity were 15% (overweight) and 14% (obesity) for boys and 16% (overweight) and 6% (obesity) for girls. The median values of fat mass percentage were closely related to the cut-off standards; however, substantial variation was noted. Boys and girls tended to be below the recommendations of cardiorespiratory fitness. Conclusions: Sport participation should be promoted in Madeira to attain acceptable values of body composition and physical fitness levels.